Does power corrupt? The moderating effect of status. (6th November 2019) - Gu, Zibei; Liu, Li; Tan, Xuyun; Liang, Yuan; Dang, Jianning; Wei, Cong; Ren, Deyun; Su, Qian; Wang, Guozhao
Abstract : Findings on the effect of power on corruption are mixed. To make sense of these mixed results, three studies were conducted to examine the moderating role of status on this effect. In Study 1, corrupt intent was measured using a corruption scenario that contained manipulations of power and status. In Study 2, corrupt behaviour was measured in a corruption game that contained manipulations of power and status. Study 3 was conducted in real organisational settings, and aimed to expand the external validity of Studies 1 and 2. The results of all three studies consistently indicated that the effect of power was moderated by status. Specifically, power increased corruption when status was low, whereas this effect disappeared when status was high. The implications of reducing the facilitating effect of power on corruption by considering status from the perspective of social hierarchy are discussed.